A systematic review of knowledge management and knowledge sharing: Trends, issues, and challenges - Muhammad Asrar-ul-Haq; Sadia Anwar (Cogent Business & Management, 2016)
This study aims to highlight and summarize the possible antecedents and factors that facilitate or impede knowledge management and knowledge sharing in organizations. A meta-review of 64 articles for the years 2010–2015 has been conducted. It includes both quantitative and qualitative studies related to antecedents and barriers to knowledge management and knowledge sharing. Cooperation bias was the most frequent limitation in most studies included in this meta-review as the respondents were likely to over-estimate their participation in knowledge management (KM) and knowledge sharing (KS). Future studies of knowledge management and knowledge sharing can be focused on exploring the same issues in developing countries in different sectors. Relationship of knowledge sharing and transfer can be further explored with social media, organizational politics, and communication in the organizations. The result of meta-review will generate nomothetic knowledge implications by scrutinizing the antecedents and barriers to knowledge sharing and transfer.
Keywords: 650